Analytical and experimental study on Ethernet passive optical networks: challenges and solutions. (6th January 2009) - Bai, Xiaofeng; Shami, Abdallah; Ye, Yinghua; Assi, Chadi M.; , Ahmad N. Khalil
Ethernet passive optical networks (EPONs) have emerged as a promising solution for the next generation access networks. As this technology matures, intensive research work is under way to enhance its functional capability and economic viability. In this work we review some existing MAC control protocols designed for EPON system. Then we study on the performance characteristic of an EPON model with both analytical and experimental approaches. By investigating the temporal relationship of multiple events successively occurring in the system, a graphical presentation is developed to facilitate more quantitative analysis. Based on classical queuing theory, we derive closed-form expression for the average packet queuing delay and average queue length of the researched EPON model. Simulation experiments show that the derived analytical expression can precisely evaluate the network performance for memoryless traffic inputs, as well as to closely estimate the performance of lightly loaded network for bursty traffic profiles.